2012
DOI: 10.1086/661936
|View full text |Cite
|
Sign up to set email alerts
|

A Motivational Account of the Question-Behavior Effect

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org. The University of Chicago Press and A Motivational Account of the Question-Behavior Effect ANNELEEN VAN KERCKHOVE MAGGIE GEUENS IRIS VERMEIRTo explain the question-behavior ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 59 publications
3
13
0
Order By: Relevance
“…The time interval between questioning and measurement of behavioural DVs varied between immediately (e.g., van Kerckhove et al, 2012) and 5 years (Murray, 1988). There was a negative relationship between time interval and the size of the QBE (β = −0.001, 95% CI = −0.002, −0.0003, p = .01; k = 91 see on-line materials Table D2), consistent with the idea that the QBE fades over time.…”
Section: Methodology Moderation Effectssupporting
confidence: 63%
See 1 more Smart Citation
“…The time interval between questioning and measurement of behavioural DVs varied between immediately (e.g., van Kerckhove et al, 2012) and 5 years (Murray, 1988). There was a negative relationship between time interval and the size of the QBE (β = −0.001, 95% CI = −0.002, −0.0003, p = .01; k = 91 see on-line materials Table D2), consistent with the idea that the QBE fades over time.…”
Section: Methodology Moderation Effectssupporting
confidence: 63%
“…Within the health area, studies have demonstrated that the QBE can be harnessed as an effective intervention to increase uptake of health screening (Sandberg & Conner, 2009), health checks (Conner, Godin, Norman, & Sheeran, 2011;Spangenberg & Sprott, 2006;Sprott, Smith, Spangenberg, & Freson, 2004;Sprott, Spangenberg, & Fisher, 2003) and vaccinations . In relation to consumer purchase behaviours, numerous studies have supported the QBE (e.g., Chandon et al, 2004;Fitzsimons & Williams, 2000;Janiszewski & Chandon, 2007;Morwitz & Fitzsimons, 2004;Morwitz, Johnson, & Schmittlein, 1993;van Kerckhove, Geuens, & Vermeir, 2012). Similarly, the QBE has been tested in prosocial behaviours such as blood donation (e.g., Cioffi & Garner, 1998;Godin, Sheeran, Conner, & Germain, 2008).…”
mentioning
confidence: 99%
“…Ideally, researchers should consider how alternate theoretical accounts could be informed within an existing study, thereby providing a competitive theory test. As noted earlier, we are aware of three comparative theory tests, all of which provide evidence against attitude accessibility yet support for three other explanations (Janiszewski & Chandon, 2007; Spangenberg et al, 2003; van Kerckhove et al, 2012a). Finally, and perhaps most importantly, clear evidence supporting “the mechanism” for the effect simply might not exist, as the question–behavior effect may well be shaped by multiple mechanisms.…”
Section: Theoretical Underpinnings Of the Question–behavior Effectmentioning
confidence: 83%
“…Of the many explanations proposed in the literature, attitude accessibility (e.g., Morwitz & Fitzsimons, 2004) and cognitive dissonance (e.g., Spangenberg & Greenwald, 1999) have arisen as the most prominent and extensively tested accounts for the effect. More recently, empirical work based on response fluency (Janiszewski & Chandon, 2007) and motivation (e.g., van Kerckhove, Geuens, & Vermeir, 2012a) has emerged. One reason that various mechanisms have been suggested for the question–behavior effect is that several cognitive or motivational processes may be active at the time of questioning and/or opportunity to perform a focal behavior, and any one, or a combination of these processes, may be responsible for subsequent behavioral change.…”
Section: Theoretical Underpinnings Of the Question–behavior Effectmentioning
confidence: 99%
See 1 more Smart Citation